2022
DOI: 10.1002/cnm.3648
|View full text |Cite
|
Sign up to set email alerts
|

Effects of axon branching and asymmetry between the branches on transport, mean age, and age density distributions of mitochondria in neurons: A computational study

Abstract: We report a computational study of mitochondria transport in a branched axon with two branches of different sizes. For comparison, we also investigate mitochondria transport in an axon with symmetric branches and in a straight (unbranched) axon. The interest in understanding mitochondria transport in branched axons is motivated by the large size of arbors of dopaminergic neurons, which die in Parkinson's disease. Since the failure of energy supply of multiple demand sites located in various axonal branches may… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…Kuznetsov and Kuznetsov (2022a, 2022b, 2023) developed an alternative model of mitochondria transport in an axon that is based on simulating mitochondria transport and accumulation in various energy demand sites. The motivation was to apply powerful methods developed for compartmental systems (Metzler et al 2018; Metzler and Sierra 2018) to determine mean age and age density distributions of mitochondria in demand sites located at different distances from the soma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuznetsov and Kuznetsov (2022a, 2022b, 2023) developed an alternative model of mitochondria transport in an axon that is based on simulating mitochondria transport and accumulation in various energy demand sites. The motivation was to apply powerful methods developed for compartmental systems (Metzler et al 2018; Metzler and Sierra 2018) to determine mean age and age density distributions of mitochondria in demand sites located at different distances from the soma.…”
Section: Introductionmentioning
confidence: 99%
“…The motivation was to apply powerful methods developed for compartmental systems (Metzler et al 2018; Metzler and Sierra 2018) to determine mean age and age density distributions of mitochondria in demand sites located at different distances from the soma. The model developed in our research was obtained by extending the model of mitochondria transport suggested in Kuznetsov and Kuznetsov (2022a, 2022b, 2023) to symmetric and asymmetric axons with multiple branching junctions (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Each demand site is represented by three compartments containing populations of anterograde, stationary, and retrograde mitochondria. We developed this model in our previous publications and utilized it for determining the mean age of mitochondria along the axon length 28 and for computing the mean age and age density distributions of mitochondria in a branching axon 29 …”
Section: Introductionmentioning
confidence: 99%
“…We developed this model in our previous publications and utilized it for determining the mean age of mitochondria along the axon length 28 and for computing the mean age and age density distributions of mitochondria in a branching axon. 29 The main question that we ask in this paper is how the mean age and age density distributions of mitochondria in the compartments located at different distances from the soma are affected by mitochondria returning to the circulation. According to our hypothesis, some of the mitochondria that exit the axon change the motors that propel them to kinesin and return to the circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Each demand site is represented by three compartments containing populations of anterograde, stationary, and retrograde mitochondria. We developed this model in our previous publications and utilized it for determining the mean age of mitochondria along the axon length [24] and for computing the mean age and age density distributions of mitochondria in a branching axon [25].…”
Section: Introductionmentioning
confidence: 99%